IMPLEMENTASI METODE TILAWATI DALAM MENINGKATKAN KEMAMPUAN MENGHAFAL AL-QUR’AN SANTRI MADRASAH DINIYAH - Novita Anggraini; Ode Mohamad Man Arfa Ladamay (JURNAL PENDIDIKAN ISLAM AL-ILMI, 2023)
The implementation of the tilawati method in improving the ability to memorize the Koran at Madrasa Diniyah Darussalam Gresik is very calculated. The tilawati method is a method of learning to read the Koran that uses tones of recitations with a balanced approach between habituation through classical and the truth of reading through individuals with the reading technique, so that in learning students can be complete and complete in reading the Koran. `an. The purpose of this research is to explore how the implementation of the tilawati method improves the ability to memorize the Koran at Madrasah Diniyah Darussalam Gresik. While this research method uses qualitative. The research subjects were the tilawati vol 2 students, each group consisting of 15 students. Researchers made observations of teacher activities which included carrying out opening activities, implementing core activities, teacher learning approaches, structuring classroom learning and implementing evaluations, besides that researchers made observations of teacher activities, also observing students' activities in learning including their fluency in reading the Koran 'an. The results of this study are that in general the implementation of the tilawati method has gone very well and has followed the procedures set by the central tilawati institution, namely opening, core, and closing